Augmented Reality and Ethnomathematics: Bringing Local Wisdom With 21st-Century Learning - Gladys Sunzuma; Lisnani Lisnani; Dini Artika Kusuma Wardhani; Zidni Naufal Fadhil (Journal of Emerging Technologies in Ethnomathematics, 2025)
The integration of Augmented Reality (AR) into ethnomathematics presents an innovative approach to preserving and promoting local cultural knowledge through modern educational technology. The aim of the study was to explore how AR can be used to enhance the teaching and learning of ethnomathematics by bringing local wisdom into 21st-century learning. Ethnomathematics, which studies the relationship between culture and mathematics, provides a unique opportunity to connect students with their cultural heritage while teaching mathematical concepts. The data for this study were collected using three primary techniques: document analysis, observations, and semi-structured interviews. The study employed a qualitative descriptive analysis, supported by content analysis and thematic coding. The findings of the study indicate that integrating Augmented Reality (AR) with ethnomathematics-based content significantly enhances students’ understanding of mathematical concepts rooted in local cultural practices. The results of the study carry several important implications for curriculum development, pedagogical practice, and future research in ethnomathematics and digital learning.